Integrating national open databases for a comprehensive view on food systems, environment sustainability and health in Brazil - Maria Julia Miele; Jacqueline Tereza da Silva; Renato Teixeira Souza; José Guilherme Cecatti; Barbara Teruel (PLoS ONE, 2025)
This paper details the integration of open-source databases on food production and consumption, pesticide use, water and land use, and nutrient supply, segmented by year and region. The process of extracting, transforming, and loading information was divided into four phases: 1) water and land use, harvest, and nutrient metrics; 2) pesticide and crop records; 3) pesticide residues with legal limits and their environment risk; 4) food acquisition and consumption by region and year. This effort resulted in 48 years of agrifood system data from 114 datasets across eight public platforms, providing a comprehensive view of the variations in agricultural production and consumption in Brazil.